Nursing care of a patient with post-herpetic neuralgia (1例带状疱疹后神经痛患者的护理体会) - SHEN Hui (申慧); CHANG Shilei (常石磊); TANG Ling (唐玲); SUN Lei (孙磊); WANG Cuiying (王翠英); LIU Tianhao (刘天浩); XIE Yingdong (解英东); ZHANG Xiangju (张香菊) (Association of Integrative Nursing, 2021)
This paper summarized the nursing experience of a patient with post-herpetic neuralgia (PHN). The patient was given a comprehensive treatment and nursing including preoperative visit, postoperative patient-controlled analgesia, postoperative visit, doctor-nurse ward round, and targeted interventions on pain, anxiety, retention of urine, etc. The doctor-nurse ward round and timely adjustment of nursing strategy are effective to improve the therapeutic effect, relieve the pain degree of post-herpetic neuralgia and improve the patient quality of life. (本文总结1例带状疱疹后神经疼痛(PHN)患者的相关护理经验, 包括术前访视、术后自控镇痛泵护理、术后回访、医护联合查房以及针对疼痛、焦虑、尿潴留等的护理措施, 通过医护联合查房及时调整护理措施可以有效提高治疗效果, 减轻PHN患者的疼痛, 提高其生活质量。)